MicroRNA-223-3p inhibits human bladder cancer cell migration and invasion - Ju Guo; Runfu Cao; Xingwei Yu; Zewen Xiao; Zhiwen Chen (Tumor Biology)
The regulation of initiation and progression during carcinogenesis of bladder carcinoma is not completely elucidated. Dysregulation of microRNAs has been detected to play critical roles in the development of various cancers, including bladder carcinoma, whereas the involvement of miR-223-3p in the tumorigenesis of bladder carcinoma has not been studied. Here, we show that significantly higher levels of nuclear receptor coactivator 1 and significantly lower levels of miR-223-3p were detected in bladder carcinoma tissue, compared to the adjacent non-tumor tissue. In addition, the levels of nuclear receptor coactivator 1 and miR-223-3p were inversely correlated. Moreover, low miR-223-3p levels in bladder carcinoma specimens were associated with poor prognosis. In vitro, depletion of miR-223-3p increased bladder carcinoma cell invasion, which was abolished by overexpression of nuclear receptor coactivator 1. Bioinformatics studies demonstrate that miR-223-3p may bind to the 3′-UTR of nuclear receptor coactivator 1 messenger RNA to inhibit its protein translation in bladder carcinoma cells. Together, our study highlights miR-223-3p as a previously unrecognized microRNA that inhibits bladder carcinoma invasiveness via nuclear receptor coactivator 1, and this finding may be important for developing innovative therapeutic targets in treating bladder carcinoma.